Influence of plasma modification of basalt fibers on the physical and mechanical characteristics of peek-based laminates - Kosmachev, P. V.; Panin, Sergey V. 1971-; Panov, I. L.; Shaimerdenova, Leyla K.; Vinnik, A. E. (Russian physics journal)
The results of a study of the effect of pre-treatment of basalt fibers with low-temperature atmospheric discharge plasma with runaway electrons on the physical and mechanical characteristics of polyetheretherketone (PEEK)-based laminates are presented. A comparison is made with the results of studies of similar composites reinforced with carbon fiber subjected to plasma treatment at the same exposure times. It is shown that the use of preliminary plasma modification leads to a significantly better wetting of the fiber surface with a polymer after 5 minutes of treatment. After a 10-minute treatment the signs of degradation of the basalt fiber surface structure are observed, accompanied by the formation of microdamages, which contributes to an increase in adhesion to the binder, but leads to a decrease in the strength characteristics of fibers and composites. When carbon fibers are processed for 10 minutes, small erosion marks appear on their surface, which contribute to an increase in interfacial adhesion, but are not so critical from the standpoint of reducing tensile strength. The revealed discrepancy in the nature of the effect of plasma treatment on basalt and carbon fiber is interpreted by differences in the conductivity properties of reinforcing materials, which affects the intensity of damage to their structure during processing, and, consequently, mechanical characteristics of the fibers and the fiber-reinforced composites.